Evaluation of the 3M™ Molecular Detection Assay (MDA) 2 – Listeria monocytogenes for the Detection of Listeria monocytogenes in a Variety of Foods and Select Environmental Surfaces: Collaborative Study, First Action 2016.08. (22nd November 2019) - Bird, Patrick; Flannery, Jonathan; Crowley, Erin; Agin, James; Goins, David; Monteroso, Lisa; ,
Abstract: The 3M™ Molecular Detection Assay (MDA) 2 – Listeria monocytogenes uses loop-mediated isothermal amplification of unique DNA target sequences combined with bioluminescence to rapidly detect Listeria monocytogenes in a broad range of food types and on environmental surfaces. Using an unpaired study design, technicians from 13 laboratories located in the United States and Canada compared the 3M MDA 2 – Listeria monocytogenes to the U.S. Department of Agriculture Food Safety Inspection Service Microbiology Laboratory Guidebook Chapter 8.09 "Isolation and Identification of Listeria monocytogenes from Red Meat, Poultry, and Egg Products, and Environmental Samples" reference method for the detection of L. monocytogenes in deli turkey and raw chicken breast fillet. Each matrix was evaluated at three levels of contamination: an uninoculated control level (0 CFU/test portion), a low inoculum level (0.2–2 CFU/test portion), and a high inoculum level (2–5 CFU/test portion). Statistical analysis was conducted according to the probability of detection (POD) statistical model. Results obtained for the low inoculum level test portions produced a difference in the collaborating laboratory POD (dLPOD) value of 0.04 with a 95% confidence interval of (−0.08, 0.17) for deli turkey, indicating that the difference between methods was not statistically significant at the 0.05 probability level. For raw chicken breast fillet, a dLPOD value of 0.16 with a 95% confidence interval of (0.04, 0.28) indicated a statistically significant difference, with an observed higher proportion of positive results by the candidate method compared to the reference method.